2020
DOI: 10.24843/jvas.2020.v03.i01.p01
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response of Bali Cattle on Anesthetic of Ketamine and Propofol

Abstract: General anesthesia in Bali cattle using ketamine and propofol has not been reported. Therefore, research is needed to determine the dosage, time of anesthesia and physiological response of ketamine, propofol, and combinations of both (ketafol). Twelve male calves, weighing 25-45 kg with age of 2-4 months were used in this research. Physiological changes in the cardiovascular and respiratory system, also body temperature was monitored using a physiograph tool. All calves were premedicated with xylazine (0.1 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In addition, there was not a great change in MAP, but a decline in RR for a long period of time (min) (15–240) was recorded in all doses. Induction of anesthesia with KET (2 mg/kg, IV) or PRO (2 mg/kg, IV) after XYL (0.1 mg/kg, IM) premedication was assessed in Bali cattle (Pemayun & Sudisma, 2020). XYL‐PRO and XYL‐KET combinations showed decreased HR up to 20 and 30 min, respectively, following induction, then began to rise gradually till the end of anesthetic period.…”
Section: Alpha2‐adrenergic Agonists In Ruminantsmentioning
confidence: 99%
“…In addition, there was not a great change in MAP, but a decline in RR for a long period of time (min) (15–240) was recorded in all doses. Induction of anesthesia with KET (2 mg/kg, IV) or PRO (2 mg/kg, IV) after XYL (0.1 mg/kg, IM) premedication was assessed in Bali cattle (Pemayun & Sudisma, 2020). XYL‐PRO and XYL‐KET combinations showed decreased HR up to 20 and 30 min, respectively, following induction, then began to rise gradually till the end of anesthetic period.…”
Section: Alpha2‐adrenergic Agonists In Ruminantsmentioning
confidence: 99%
“…The condition of mucus coupled with double dosage AI at the 2nd hour AI and 8th hour AI makes the PR pregnancy rate high [10]. Signs of oestrus in cows are characterized by restlessness, swelling and redness of the vulva, decreased milk production, discharge, or clear translucent mucus from the vulva [14] The effect of vulvar swelling on NRR in this study is shown in Table 9. Dosage 1 showed that the vulvar swelling in the very swollen category has a percentage of 62.22% in NRR-1 and in NRR-2 it has a value of 60.00%.…”
Section: Effect Of Vaginal Temperature On Non-return Rate-1 Non-retur...mentioning
confidence: 89%